2019
DOI: 10.1016/j.nlm.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Trax: A versatile signaling protein plays key roles in synaptic plasticity and DNA repair

Abstract: Translin-associated protein X (TSNAX), also called trax, was first identified as a protein that interacts with translin. Subsequent studies demonstrated that these proteins form a heteromeric RNase complex that mediates degradation of microRNAs, a pivotal finding that has stimulated interest in understanding the role of translin and trax in cell signaling. Recent studies addressing this question have revealed that trax plays key roles in both synaptic plasticity and DNA repair signaling pathways. In the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In addition to its well-known role in mediating DNA repair, this kinase also plays a prominent role in regulating insulin signaling [6]. Thus, adiposity displayed by translin KO mice might reflect dysregulation of ATM signaling pathways [5, 47]. Second, the translin/trax complex has been shown to bind to the glucose response element of the LPK gene in rat liver extracts and cultured hepatocytes [48, 49], so it may regulate LPK transcription in a microRNA-independent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its well-known role in mediating DNA repair, this kinase also plays a prominent role in regulating insulin signaling [6]. Thus, adiposity displayed by translin KO mice might reflect dysregulation of ATM signaling pathways [5, 47]. Second, the translin/trax complex has been shown to bind to the glucose response element of the LPK gene in rat liver extracts and cultured hepatocytes [48, 49], so it may regulate LPK transcription in a microRNA-independent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Translin, a nuclear protein that is phylogenetically conserved in eukaryotes, constitutes a hetero-octamer together with Translin-associated factor X (TRAX) [reviewed in 1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Because TRAX is a scaffold protein that acts by interacting with different proteins of distinct functions, 35 we hypothesized that TRAX and its specific binding partner under certain pathophysiological conditions may be regulated in the same manner. Earlier studies demonstrated that the expression of A 2A R (an interacting protein of TRAX) is downregulated during HD progression in humans and mice with HD 29,36 .…”
Section: Resultsmentioning
confidence: 99%